Pemetaan Spasial Keterkaitan Faktor Risiko Kematian Neonatal dengan Mixed Geographically Weighted Regression - Cinta Rizki Oktarina; Sri Syuhada Putri; Reza Pahlepi; Avrillia Permata Hati4; Dyah Setyo Rini (Lembaga Pengembangan Kinerja Dosen, 2024)
Neonatal mortality is a major issue in developing countries, particularly in Indonesia. Data reveals that Neonatal Mortality Rate (NMR) contributes to 59% of infant deaths in Indonesia. Infant mortality rates remain high in Indonesia, at 20 per 1,000 live births. West Java has recorded a significant decline in neonatal mortality rates, dropping from 9.9 per 1,000 live births in 2019 to 9 per 1,000 in 2021. Factors influencing neonatal mortality have been extensively studied, including through the Mixed Geographically Weighted Regression (MGWR) method. The MGWR model combines local and global models, generating parameter estimators that are both local and global according to the observation locations. This research uses secondary data from the health profile of West Java, with the dependent variable being the number of neonatal deaths in 27 districts/cities in the year 2020. MGWR analysis results indicate that congenital anomalies have a local impact, while low birth weight and complete neonatal visits affect the entire West Java region globally. This study offers vital insights into the factors contributing to neonatal mortality in West Java and can serve as a foundation for targeted policy improvements and healthcare interventions